Application of carbon dioxide to the skin and muscle oxygenation of human lower-limb muscle sites during cold water immersion - Yoshimura, Miho; Hojo, Tatsuya; Yamamoto, Hayato; Tachibana, Misato; Nakamura, Masatoshi; Tsutsumi, Hiroaki; Fukuoka, Yoshiyuki (PeerJ, 2020)
Background Cold therapy has the disadvantage of inducing vasoconstriction in arterial and venous capillaries. The effects of carbon dioxide (CO2) hot water depend mainly on not only cutaneous vasodilation but also muscle vasodilation. We examined the effects of artificial CO2 cold water immersion (CCWI) on skin oxygenation and muscle oxygenation and the immersed skin temperature. Subjects and Methods Fifteen healthy young males participated. CO2-rich water containing CO2 >1,150 ppm was prepared using a micro-bubble device. Each subject’s single leg was immersed up to the knee in the CO2-rich water (20 °C) for 15 min, followed by a 20-min recovery period. As a control study, a leg of the subject was immersed in cold tap-water at 20 °C (CWI). The skin temperature at the lower leg under water immersion (Tsk-WI) and the subject’s thermal sensation at the immersed and non-immersed lower legs were measured throughout the experiment. We simultaneously measured the relative changes of local muscle oxygenation/deoxygenation compared to the basal values (Δoxy[Hb+Mb], Δdeoxy[Hb+Mb], and Δtotal[Hb+Mb]) at rest, which reflected the blood flow in the muscle, and we measured the tissue O2 saturation (StO2) by near-infrared spectroscopy on two regions of the tibialis anterior (TA) and gastrocnemius (GAS) muscles. Results Compared to the CWI results, the Δoxy[Hb+Mb] and Δtotal[Hb+Mb] in the TA muscle at CCWI were increased and continued at a steady state during the recovery period. In GAS muscle, the Δtotal[Hb+Mb] and Δdeoxy[Hb+Mb] were increased during CCWI compared to CWI. Notably, StO2values in both TA and GAS muscles were significantly increased during CCWI compared to CWI. In addition, compared to the CWI, a significant decrease in Tsk at the immersed leg after the CCWI was maintained until the end of the 20-min recovery, and the significant reduction continued. Discussion The combination of CO2 and cold water can induce both more increased blood inflow into muscles and volume-related (total heme concentration) changes in deoxy[Hb+Mb] during the recovery period. The Tsk-WI stayed lower with the CCWI compared to the CWI, as it is associated with vasodilation by CO2.
Keywords: CO2-rich; Cold water immersion; Near-infrared spectroscopy; Skin temperature; Muscle oxygenation; Lower-limb muscle